The Role of the Mirror System in Influencing Musicians’ Evaluation of Musical Creativity: A tDCS Study - Colombo, Barbara; Anctil, Reid; Balzarotti, Stefania; Biassoni, Federica; Antonietti, Alessandro (Frontiers in Neuroscience, 2021)
Evidence reported in the literature suggests that the mirror system not only plays a role in recognizing motor action, but it also fosters a better understanding of others because it helps an individual assume the others' perspective. This led to the idea, supported by research findings, that people with higher empathy scores should also show higher activation of the mirror system. Recently it has been hypothesized that a purely auditory mirror system exists. In this study, we aim at exploring the possibility that this system might play a specific role for musicians in response to a new piece of music by using non-invasive brain stimulation to modulate the activation of the mirror system. A sample of 40 young musicians was involved in this pilot study. Half of the participants were randomly assigned to a cathodal stimulation condition, while the other one was used as control. After listening to a new piece of music, participants were asked to rate the creativity of the piece (by focusing on how interesting, innovative, and exiting the piece was) as well as their general emotional response to it. Their empathy levels were also assessed using the IRI. Results showed that the cathodal stimulation of the mirror system negatively affected both the perception of creativity and the emotional response to the music, through ratings of innovation and excitement respectively. There was no significant difference in the rating of how interesting the piece was perceived. The effect was mediated by the individuals' level of empathy. Specifically, empathic concern and fantasy scale increased the evaluation of creativity. Results also showed that cathodal stimulation participants reported less emotion with a negative valence.